Indomie sebagai Agen Globalisasi Budaya: Ekspansi Produk Indonesia di Afrika dalam Kerangka Indonesia–Africa Infrastructure Dialogue - Putri, Nabila Aisyah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
The expansion of Indomie products into Africa reflects new dynamics in the economic and cultural relations of the Global South. Through collaboration between PT Indofood CBP Sukses Makmur Tbk and Tolaram Group, Indomie is not only present as a consumer product, but also plays a role in shaping cultural identity in African countries such as Nigeria, Ghana, and Egypt. This study highlights how this expansion is supported by corporate diplomacy and strategic cooperation through the Indonesia–Africa Infrastructure Dialogue (IAID). Using a qualitative literature-based study method, this research analyzes the role of non-state actors in mediating the flow of cultural globalization in Africa. The results of the study show that Indomie has transformed into a cultural agent that influences the consumption patterns and lifestyles of local communities. This product has also created a form of cultural hybridization through the adaptation of local flavors and integration into daily life. However, this success also presents challenges related to symbolic dominance and the transformation of local values. These findings demonstrate that economic and cultural diplomacy can be intertwined in the context of contemporary international relations, and emphasize the importance of understanding consumer products as a means of disseminating cultural values and transforming identity in the era of contemporary globalization.